Improved cell-penetrating peptide–PNA conjugates for splicing redirection in HeLa cells and exon skipping in mdx mouse muscle - Ivanova, Gabriela D. (Oxford University Press, 2008)
Steric blocking peptide nucleic acid (PNA) oligonucleotides have been used increasingly for redirecting RNA splicing particularly in therapeutic applications such as Duchenne muscular dystrophy (DMD). Covalent attachment of a cell-penetrating peptide helps to improve cell delivery of PNA. We have used a HeLa pLuc705 cell splicing redirection assay to develop a series of PNA internalization peptides (Pip) conjugated to an 18-mer PNA705 model oligonucleotide with higher activity compared to a PNA705 conjugate with a leading cell-penetrating peptide being developed for therapeutic use, (R-Ahx-R)(4). We show that Pip–PNA705 conjugates are internalized in HeLa cells by an energy-dependent mechanism and that the predominant pathway of cell uptake of biologically active conjugate seems to be via clathrin-dependent endocytosis. In a mouse model of DMD, serum-stabilized Pip2a or Pip2b peptides conjugated to a 20-mer PNA (PNADMD) targeting the exon 23 mutation in the dystrophin gene showed strong exon-skipping activity in differentiated mdx mouse myotubes in culture in the absence of an added transfection agent at concentrations where naked PNADMD was inactive. Injection of Pip2a-PNADMD or Pip2b-PNADMD into the tibealis anterior muscles of mdx mice resulted in ∼3-fold higher numbers of dystrophin-positive fibres compared to naked PNADMD or (R-Ahx-R)(4)-PNADMD.